Modified Anterior Temporal Lobectomy: Anatomical Landmarks and Operative Technique - Ghizoni, Enrico; Almeida, J. P.; Joaquim, Andrei F.; Yasuda, Clarissa L.; de Campos, Brunno M.; Tedeschi, Helder; Cendes, Fernando (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2015)
There is great controversy about which surgical approach is the most selective and efficient for resection of mesial structures of the temporal lobe for treatment of mesial temporal lobe epilepsy. Selective approaches have been described in an attempt to preserve the neocortex and the temporal stem. Nonselective approaches, such as anterior temporal lobectomy (ATL), result in injuries in these structures. We describe a modified selective technique for resection of the amygdala and hippocampus with resection of the temporal pole performed through the Sylvian fissure based on anatomical landmarks and diligent microsurgical techniques. Briefly, after opening the Sylvian fissure, the temporal pole is resected and the temporal horn is directly accessed through the uncus, in an anteroposterior direction, preserving the temporal stem and the neocortex of the temporal lobe. The surgical technique used by our group is described in detail with illustrations. Precise microsurgical techniques associated with knowledge of microsurgical anatomy are of paramount importance for temporal lobe epilepsy surgery. According to our analysis, the modified ATL approach to the temporal mesial structures is a feasible selective technique that can be used as an alternative to traditional surgical procedures.
Keywords: epilepsy; uncus; transsylvian; amygdala; anatomy